Pengaruh Kombinasi Terapi Musik Dan Art Therapy Terhadap Tingkat Nyeri Pasien Kanker Payudara - Maria Kurnyata Rante Kada; Dewi Irawaty; Riri Maria (Jurnal Keperawatan Muhammadiyah, 2020)
Background : Cancer pain is a multidimensional experience of cancer patients that can affect all dimensions of the quality of life of patients. The capacity of one's attention to a condition is very limited, therefore to reduce the capacity of the process of pain required distraction or input of a strong stimulus that is fun, one of them with a combination of art therapy and music therapy. Objective : This study aims to determine the effect of a combination of music therapy and art therapy to the level of pain in breast cancer patients. Methode : This study uses quasi-experimental design involving 34 respondents selected by purposive sampling. Results : The results of this study indicate that there are significant differences in the level of pain after treatment between groups who only receivedÂ standard analgesic and groups who received a combination of music therapy and art therapy with p-value = 0.008 (p <0.05). Based on the results of the study, it can be concluded that the combination of music therapy and art therapy is more effective for reducing pain in people living with breast cancer than only standard analgesic. Conclusion : The results of this study can be one of the intervention recommendations to reduce pain in breast cancer sufferers and encourage independence in the autonomy role of nurses.Keywords: art therapy, pain, breast cancer